Rethinking the Musical Instrument - Doğantan-Dack, Mine (Newcastle upon Tyne Cambridge Scholars Publishing, 2022)
This volume brings together scholars and artist-researchers to explore the nature and function of musical instruments in creative practices, and their role in musical culture. Through historical, theoretical, critical, practical-artistic perspectives and case studies, the contributors here examine identities and affordances of acoustical, electronic and digital musical instruments, the kinds of relationships that composers and performers establish with them, and the crucial role they play in the emergence of musical experiences and meanings.
Keywords: Organology; Artistic research